A preliminary description of the syntax and morphology of interrogatives in the Shona language (Journal for Studies in Humanities and Social Sciences, 2019)
This article describes some idiosyncratic properties of interrogative particles in the Shona language from the view point of their morphological and syntactic behaviour. This arises out of the observation that in syntactic structure, there are instances in which interrogatives can substitute for the nouns about whose enquiry they are made. It would make an interesting study to determine the extent to which interrogatives can stand as surrogate nouns. Shona marks for interrogatives using both segmental and supra-segmental strategies. The following are examples of segmental interrogative markers: sei ‘why’, ko? ‘Why/how come’, saka? ‘so?’, -ei? ‘why?’, chii? ‘what?’, ani? ‘who?’, -i? ‘what/when/which?’, ngani? ‘How many?’. Supra-segmentals generally use the strategy of placing high tone marking on specific segments. Moreover certain interrogatives can simultaneously combine within the same interrogative sentence, chiefly for emphasis. At the same time, there are some interrogatives that are not compatible with each other. In addition, interrogatives seem to have semantic features that are generally associated with [±Human], [±Count], [±Affirmation], etc., in addition to the common feature [+Interrogative]. This paper sought to examine how these features influence the syntax of interrogative sentences in terms of the compatibility and incompatibility properties of certain interrogative particles as well as determine how the same features pro-actively and ‘intelligently’ select the range of potential answers in the Shona language.